2011
DOI: 10.1007/s11033-011-1153-z
|View full text |Cite
|
Sign up to set email alerts
|

A promoter polymorphism of MSTN g.−371T>A and its associations with carcass traits in Korean cattle

Abstract: A promoter polymorphism of bovine Myostatin (MSTN) gene g.-371T>A was screened in Holstein and two Korean indigenous cattle breeds, Hanwoo and Jeju Black cattle (JBC). The MSTN g.-371T>A polymorphism was found in all three cattle breeds tested. An allele MSTN g.-371A was the most frequent in the JBC breed among breeds tested. The association of MSTN genotypes for carcass traits was also tested in the Hanwoo population. Significant differences were found between the genotypes and level of meat quality grade ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
8

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 37 publications
3
12
0
8
Order By: Relevance
“…Results of the present studies support those obtained by other authors who demonstrated that the A allele frequency was low in a number of analysed cattle breeds [12].…”
Section: Itemsupporting
confidence: 92%
“…Results of the present studies support those obtained by other authors who demonstrated that the A allele frequency was low in a number of analysed cattle breeds [12].…”
Section: Itemsupporting
confidence: 92%
“…Polymorphisms in the MSTN gene have been correlated to production traits, making it a candidate target gene to enhance livestock and fowl productivity (Lu et al, 2011;Han et al, 2012 andZhang et al, 2012). However, in many cases, the allele associated with favourable production traits is not always favourable for reproductive traits.…”
Section: Introductionmentioning
confidence: 99%
“…Nasr et al, (2016) reported that allele and gene frequencies were homozygot for MSTN gene in Holstein bull (AA). Han et al (2012) investigated that the relationship between MSTN g.-371T>A gene and carcass characteristics in Korean cattle. For this purpose, three different genotypes using DraI restriction enzymes have identified in Holstein, Juju Black Cattle and Hanwoo breeds.…”
Section: Resultsmentioning
confidence: 99%